The Exponential Cubic B-Spline Algorithm for Korteweg-de Vries Equation. (17th February 2015) - Ersoy, Ozlem; Dag, Idris
Abstract : The exponential cubic B-spline algorithm is presented to find the numerical solutions of the Korteweg-de Vries (KdV) equation. The problem is reduced to a system of algebraic equations, which is solved by using a variant of Thomas algorithm. Numerical experiments are carried out to demonstrate the efficiency of the suggested algorithm.